ZCT 104E/3 - Fizik IV (Modern Physics) - February - March 2003 - PPSF, Pusat Pengajian Sains Fizik (2003)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2002/2003 Academic Session February — March 2003 ZCT 104E/3 - Fizik IV (Modern Physics) Time : 3 hours